Clinical, Radiographic and Analytical Findings of Atypical Rabies Encephalitis in a Five-Year-Old Boy: A Case Report - Gupta, Manoj Kumar; Acharya, Prakriti; Jha, Aman; Paudel, Prabin (Med Phoenix, 2023)
Introduction: Rabies is an almost always fatal disease that doctors and patients fear because of its bleak prognosis and limited treatment choices. In the absence of special laboratory investigations at the point-of-care facility, the diagnosis is usually clinical. We present a case of rabies encephalitis with a dog bite history and standard MRI findings that can be used for early identification in the absence of usual clinical signs and specialized diagnostic testing.